2008
DOI: 10.1021/jp077098p
|View full text |Cite
|
Sign up to set email alerts
|

Keggin Polyoxoanions in Aqueous Solution: Ion Pairing and Its Effect on Dynamic Properties by Molecular Dynamics Simulations

Abstract: The dynamics of Keggin polyoxoanions in aqueous solution in the presence of monovalent cations is analyzed through molecular dynamics simulations. Together with structural information yielding the radial distribution functions of Li(+), Na(+), and K(+) with three polyoxometalates (POMs) bearing 3-, 4-, and 5- charges, the diffusion coefficient of these POMs is calculated. We found that the effect of the microscopic molecular details of the solvent is a key aspect to interpreting the structural and dynamic data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(112 citation statements)
references
References 61 publications
6
104
0
2
Order By: Relevance
“…Indeed, MM simulations performed on Keggin polyoxoanions by Leroy et al highlight the key role of the solvent, which acts as a mediator in the interactions between the anion and some cations, where "a competition between electrostatic interactions between the ions and the stability of the solvation shell is established." 17 We have also shown that some metal-oxygen bonds in hepta-anions exhibit a high sensitivity towards the solvent resulting in a poor agreement between the calculated and the experimental bond length. 18 This influence of solvent and counterions on the structural properties of the POMs also has been underlined for octamolybdate isomers, which contain four-coordinated Mo atoms in water, which tend to become threecoordinated when isolated.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Indeed, MM simulations performed on Keggin polyoxoanions by Leroy et al highlight the key role of the solvent, which acts as a mediator in the interactions between the anion and some cations, where "a competition between electrostatic interactions between the ions and the stability of the solvation shell is established." 17 We have also shown that some metal-oxygen bonds in hepta-anions exhibit a high sensitivity towards the solvent resulting in a poor agreement between the calculated and the experimental bond length. 18 This influence of solvent and counterions on the structural properties of the POMs also has been underlined for octamolybdate isomers, which contain four-coordinated Mo atoms in water, which tend to become threecoordinated when isolated.…”
Section: Introductionmentioning
confidence: 89%
“…Few attempts of MM simulations have been performed using optimized force fields dedicated to inorganic compounds, and either the electrostatic interactions are neglected 20,21 or determined based on potential-derived charges. 17,22 To describe the electrostatic and van der Waals interactions, the nonbonded potential, V nonbonded , needs to be considered and optimized. This term also encompasses all the interactions between atoms that are not transmitted through the bonds.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the relevance of contacts between PKAs and alkali metal countercations was also studied in detail by Chaumont 66,69 In any case, countercations were reported to often act as an outright "electrostatic glue", promoting the formation of Keggin anion oligomers.…”
Section: A Cationic Gluementioning
confidence: 99%
“…35 In another study, López et al 65 have reported simulations of the α-PKA salt Na 3 PW 12 O 40 in water, carrying out a detailed analysis of the distribution and orientation of water molecules at different sites around the anion. Three years later 66 66 the authors did indeed observe PKA aggregation as a function of concentration, PKA charges, and cation type (albeit rarely surviving beyond 0.5-0.8 ns): cations were seen to mediate aggregation by crucially overcoming the negative charge on PKAs, effectively "gluing" them together.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the counter cation on the redox properties of POM anions has been documented in the recent literature, ascribed to formation of ion pairs, [79][80][81][82] which might lead to a modification of the effective charge of the POMs, thus affecting their solvation and modifying their catalytic behavior. [35,[83][84][85] Furthermore, a secondary effect is expected because of the different conductivity of the three alkali cations in aqueous solution. [86] This induces a differential MW www.chemeurj.org absorption, and a consequent difference for the heating profiles and distribution of the so-called overheated zones (hot spots) of the solvent, which also affect the oxidation rate.…”
Section: Solution Magnetic-moment Determination and Epr Spectrummentioning
confidence: 99%